Analisis Kinerja Keuangan PDAM Tanah Toraja dengan EVA 2020-2022 - Paulus, Shelin; Machmud, Mulyana; Suwandi, Suwandi; Nisrina, Ulfah Laila (Jurnal Ilmiah Manajemen & Kewirausahaan, 2023)
Analysis of Economic Value Added (EVA) as a measuring tool for the financial performance of the Regional Drinking Water Company (PDAM) in Tanah Toraja Regency. The purpose of this research is to find out how the financial performance of the Regional Drinking Water Company (PDAM) in Tanah Toraja Regency is measured using the Economic Value Added (EVA) Method. The analytical method used in this study is to use a quantitative method with a descriptive analysis model. The sample used is the financial statements in the form of income statements and balance sheets. primary and secondary data types, with data collection techniques namely observation, interviews, documentation, and literature research. These results indicate that within 3 years, from 2020 to 2022, the negative EVA value has decreased, EVA < 0 . This can be seen from the results of the EVA analysis from 2020 to 2022 for the Regional Drinking Water Company (PDAM) of Tanah Toraja Regency which has a negative value and is below zero, namely in 2020 the EVA for the Regional Drinking Water Company (PDAM) of Tanah Regency Toraja is (Rp.6.300.442), in 2021 it is (Rp.7.272.384) and in 2022 EVA is (Rp.6.914.619). A negative EVA means that the financial performance of the Toraja Regional Drinking Water Company (PDAM) is unhealthy or does not experience added economic value for the company.